Global Product Development Proceedings of the 20th CIRP Design Conference, Ecole Centrale de Nantes, Nantes, France, 19th-21st April 2010 - Bernard, Alain; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book of proceedings is the synthesis of all the papers, including keynotes presented during the 20th CIRP Design conference. The book is structured with respect to several topics, in fact the main topics that serve at structuring the program. For each of them, high quality papers are provided. The main topic of the conference was Global Product Development. This includes technical, organizational, informational, theoretical, environmental, performance evaluation, knowledge management, and collaborative aspects. Special sessions were related to innovation, in particular extraction of knowledge from patents.
General trends in global product developments -- Evolutions of global product development approaches -- Early stage design in global product development -- Ecological Aspects in global product development -- Models and Methods for Variation Management in global product development -- Requirements management in global product development -- Collaborative Aspects in global product development -- Integration Product-Process in global product development -- Product Design Models for global product development -- Product design methods for global product development -- Value, Risk and Cost Management in global product development -- Knowledge Management for creative and inventive design in global product development -- Patents as resources for Creative and Inventive Design for global product development -- Metrics and Benchmarking, performance evaluation for global product development -- Rapid Product Development, Reverse Engineering, Virtual Reality for global product development.
Keywords: Engineering; Computer aided design; Engineering design; Sustainable development; Engineering; Engineering Design; Computer-Aided Engineering (CAD, CAE) and Design; Innovation/Technology Management; Sustainable Development